"The Third Time Janus Died": Resilience and Dependencies In Coping With Adversity During And After Civil War In Northern Uganda. Issue 2 (3rd July 2022) - Harnisch, Helle
ABSTRACT: This article critically explores how local notions of coping and resilience among former forcibly recruited children and youth in the war-affected Acholi region resonate with established conceptualisations of resilience in resilience research that primarily originate from a US context. Based on 12 months of fieldwork in urban and rural Acholi contexts, the analysis shows how poverty, corruption, and the presence of international humanitarian organisations in the urban context, create dependencies that diminish community resilience in the Acholi region. The findings call for optimising the balance between emic and etic perspectives in resilience studies as well as in humanitarian interventions.